A Survey High Performance Storage in Data Center - Irma Nurfitri Handayani; Ruki Harwahyu (Ikatan Dosen Menulis, 2024)
According to statistics, by 2025, It will be storing approximately 160 zettabytes of data. This increase causes data centers to be fast in innovating, to meet user needs. Currently, most data centers still use traditional storage mechanisms. The rapid growth of enterprises and customers requires access to storage that is easy to access, innovates and more dynamic in management, reduces costs in development and maintenance, and requires increased scalability. In this survey discuss past and ongoing uses of storage to increase high performance storage technology and storage system